Asymmetric Dearomatization of Indole Derivatives with N‐Hydroxycarbamates Enabled by Photoredox Catalysis - Cheng, Yuan‐Zheng; Zhao, Qing‐Ru; Zhang, Xiao; You, Shu‐Li (Angewandte Chemie International Edition, 2019)
Dearomatization of indoles provides efficient synthetic routes for substituted indolines. In most cases, indoles serve as nucleophiles. Reported here is an asymmetric dearomatization reaction of indole derivatives that function as electrophiles. The combination of a photocatalyst and chiral phosphoric acid open to air unlocks the umpolung reactivity of indoles, enabling their dearomatization with N‐hydroxycarbamates as nucleophiles. A variety of fused indolines bearing intriguing oxy‐amines were constructed in excellent yields with moderate to high enantioselectivities. Mechanistic studies show that the realization of two sequential single‐electron transfer oxidations of the indole derivatives is key, generating the configurationally biased carbocation species while providing the source of stereochemical induction. These results not only provide an efficient synthesis of enantioenriched indoline derivatives, but also offer a novel strategy for further designing asymmetric dearomatization reactions. Unlocked: Dearomatization of indoles and their derivatives provides efficient synthetic routes for substituted indolines. For this asymmetric dearomatization reaction the indoles function as electrophiles. The combined utilization of a photocatalyst and chiral phosphoric acid (CPA) open to air unlocks the umpolung reactivity of indoles, enabling enantioselective dearomatization of indoles with N‐hydroxycarbamates as nucleophiles.